Air stream velocity modelling in multichannel spiral cyclone separator - Vaitiekūnas, Petras; Petraitis, Egidijus; Venslovas, Albertas; Chlebnikovas, Aleksandras (Journal of Environmental Engineering and Landscape Management, 2014)
Numerical modelling problem is investigated in a gas aerodynamics multichannel spiral cyclone separator with a tangential inflow. Experimental and theoretical papers analysing cyclone separator with particularly complex turbulent flow were reviewed. The three-dimensional transport differential equations for incompressible laminar and turbulent flow inside the cyclone separator were presented. They were numerically solved by finite volume method using the Re-Normalisation Group (hereinafter RNG) k-ε turbulence model. The numerical air flow movement was modelled in cyclone separator with the following dimensions: 0.95 m height, 0.330 m diameter, 0.88 m height of spiral-cylindrical part, 0.39 m height of conical part, inflow dimensions (on the side of cylindrical part) according to the drawings were a × b = 28 × 95 mm. The mathematical model of air flow movement in cyclone separator was composed by Navier-Stokes (Reynolds) as the three-dimensional differential equation system. The modelling results were obtained by the tangential and axial velocity profiles in cyclone separator using RNG k-ε turbulence model, the inflow velocity from 4.1 m/s to 15.4 m/s coincided well with the experimental results. This is the first article testing for multichannel cyclone and determined distributions of aerodynamic parameters. The absolute error between experimental and modelling results changed from 0.01 to 0.24 units.